A La3+-selective metallohydrogel with a facile gelator of a phenylalanine derivative containing an imidazole group. Issue 39 (25th September 2018) - Wei, Chuan-Wan; Wang, Xiao-Juan; Gao, Shu-Qin; Wen, Ge-Bo; Lin, Ying-Wu
Abstract : The first La 3+ -selective metallohydrogel was successfully constructed by using a facile gelator of a phenylalanine derivative containing an imidazole group, namely La-ImF. Abstract : The first La 3+ -selective metallohydrogel was constructed by using a facile gelator of a phenylalanine derivative containing an imidazole group, N -(1 H -imidazol-4-yl)methylidene-l -phenylalanine, namely La-ImF, which exhibits multi-stimuli responsive properties, including to heat, shearing, pH, etc . Various measurements were also carried out to obtain insights into the mechanism of gelation. Moreover, the La-ImF hydrogel can adsorb toxic dyes, making it a potential candidate for sewage treatment.